Strategi Corporate Social Responsibility untuk Transformasi Bisnis dalam Membangun Masa Depan yang Berkelanjutan - Nafi’ul Umam; Nazaruddin Malik; Masiyah Kholmi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the era of globalization, companies not only focus on financial resources but also social and environmental aspects of their activities. Corporate Social Responsibility (CSR) is essential for companies to adapt and grow, foster relationships with stakeholders, mitigate risks, and create value for society. Interdisciplinary research is essential to understand the importance of CSR in business transformation. This research utilizes a qualitative descriptive research methodology. In CSR implementation, the presence of sustainable leaders is the presence of leaders who have a vision and mission can help companies in developing effective and sustainable CSR strategies. They can help companies in improving reputation and public trust, strengthening relationships with stakeholders, and opening new market opportunities. Stakeholder interest in CSR is an influence in improving CSR effectiveness and business transformation. They can increase community awareness and participation in development and empowerment efforts, and assist companies in improving effective and sustainable CSR strategies.